PREDICTION OF CARDIAC ARRHYTHMIA USING RECURRENT NEURAL NETWORKS GATED RECURRENT UNITS WITH CAUSAL DIAGRAM - U.M. Prakash; Chakravarthi, Anagha; Shekhawat, Gargi Singh (International Journal of Psychosocial Rehabilitation, 2020)
Cardiac Arrhythmia is a medical condition in which irregularity in the heart beat is observed. The aim of this paper is to detect said arrhythmia using a dataset containing various patient details. A popular technique is used namely Recurrent neural networks (RNN) in which a comparatively newer technique is used i.e. Gated recurrent units. This is again implemented with the observations from causality diagram to localize on the right attributes to work with.